Analyzing long lasting effects of environmental policies: Evidence from low, middle and high income economies - Ozcan, Burcu; Ulucak, Recep; Dugan, Eyup (Elsevier, 2019)
This study investigates whether or not environmental policies have long lasting effects by analyzing stochastic properties of ecological footprint that recently attracts a great attention and is accepted as a broader measure of the environmental degradation in the literature. To this end, countries are classified by income groups and the panel KSS unit root test alongside the SPSM procedure are utilized based on the annual data from 1961 to 2013. The empirical results show that ecological footprint has stationary process for all high-income countries and for about the half of the low-income and upper-middle income economies, whereas non-stationarity is verified for the lower-middle income economies. Crucial policy implications are further discussed.
Keywords: Environmental damage; Ecological footprint; Persistence; Stationarity; SPSM